Microbial and chemical stability of lumpfish (Cyclopterus lumpus) roe during refrigerated storage in acid-salt brines with or without antioxidants - Jensen, Hanne Aarslev; Plaza, Laura Garcia; Houmann, Rannvá Høgnadóttir; Andreasen, Pernille Bak; Bøknæs, Niels; Kragh, Martin Laage; Hansen, Lisbeth Truelstrup; Mejlholm, Ole; Jacobsen, Charlotte; Dalgaard, Paw; Sørensen, Ann-Dorit Moltke (Frontiers in Food Science and Technology, 2024)
Immediately after the harvest of lumpfish (Cyclopterus lumpus) roe in artic regions, a common practice is to preserve the fresh roe in brine to produce a salted intermediate product (SIP), which can be transported and stored refrigerated for up to one year prior to retail processing. Because the roe is susceptible to microbial growth and lipid oxidation, the brines have been composed of mixes of salt (>10%) and benzoic acid to manage the quality and safety of the SIP. However, a demand for reducing the use of salt and benzoic acid is appearing on the European market. Therefore, the aim of this study was to evaluate the effect of five different brines comprised of combinations of salt, organic acids, and antioxidants on controlling microbial and chemical changes of the SIP, to be able to avoid the use of benzoic acid and reduce the salt content. Freshly harvested roe was mixed with brines to obtain 7 or 10% (w/w) NaCl and combinations of acetic, benzoic and/or lactic acids with or without addition of VivOx 7.5 (IFF Inc.) or Herbalox D-450 (Kalsec Inc.) as antioxidants. Brined roes were stored refrigerated (1.94±0.56 °C) with sampling after 50, 80, 120, 210, 288 and 353 days. Regardless of the treatment applied, aerobic viable counts increased to >6.1 log CFU/g after 120 days of storage and the microbiota in all treatments became dominated by Debaromyces hansenii as identified using MALDI-TOF and metagenome sequencing. The addition of antioxidants reduced the formation of lipid hydroperoxides and thiobarbituric acid reactive substances. Both Herbalox and VivOx reduced the formation of 1-penten-3-ol, whereas VivOx increased the formation of pentanal in the roe. Concentrations of 2-methyl-butanol and 3-methyl-butanol were markedly reduced by treatments that included benzoic acid, which may be related to differences in the activity of the microbiota. Herbalox was more efficient than VivOx in reducing oxidative changes whereas the effect of organic acids on oxidative alterations remained inconclusive. In conclusion, it was possible to reduce the salt content and avoid the use of benzoic acid without affecting the microbial and oxidative stability of the SIP as well as its safety.